Remaining Service Life (RSL) Struktur Conveyor A pada Tambang Batubara PT XYZ di Kabupaten Kotabaru Provinsi Kalimantan Selatan - Reka Juliantika; Elfida Moralista; Iswandaru (UNISBA Press, 2022)
Abstract. Conveyor structures are used in the mining industry as a tool that supports the processing of minerals to move excavated materials from one place to another. The conveyor structure is made of carbon steel which is subject to corrosion. The occurrence of corrosion can cause a reduction in the service life of the conveyor structure. The purpose of this research is to determine the type of corrosion, corrosion rate, remaining life, and coating method as its control. This research was conducted on a 90 meter long conveyor structure which is divided into 3 segments with 25 test points. Measurement of the reduction in the thickness of the conveyor structure using the Ultrasonic Thickness Gauge TT 130. The type of corrosion that occurs in the conveyor structure is a type of uniform corrosion. This corrosion control uses a three-layer coating method with Seaguard 5000 primer coating, Sherglass FF intermediate coating, and aliphatic acrylic modified polyurethane top coating. The corrosion rate of the conveyor structure ranges from 0.1550-0.3050 mm/year which is included in the good category based on the table of the relative corrosion resistance of steel, thus there are 44% or 11 test points which are predicted to not reach the design life of 15 years. Abstrak. Struktur conveyor digunakan pada industri pertambangan sebagai alat yang menunjang dalam proses pengolahan bahan galian untuk memindahkan material bahan galian dari satu tempat ketempat lain. Struktur conveyor terbuat dari baja karbon yang dapat mengalami korosi. Terjadinya korosi dapat menyebabkan pengurangan umur pakai pada struktur conveyor. Tujuan dilakukannya penelitian ini adalah untuk mengetahui jenis korosi, laju korosi, sisa umur pakai, serta metoda coating sebagai pengendaliannya. Penelitian ini dilakukan pada struktur conveyor sepanjang 90 meter yang terbagi menjadi 3 segmen dengan 25 test point. Pengukuran pengurangan ketebalan struktur conveyor menggunakan alat Ultrasonic Thickness Gauge TT 130. Jenis korosi yang terjadi pada struktur conveyor merupakan jenis korosi merata. Pengendalian korosi ini menggunakan metoda coating tiga layer dengan primer coating Seaguard 5000, intermediate coating Sherglass FF, dan top coating aliphatic acrylic modified polyurethane. Laju korosi struktur conveyor berkisar antara 0,1550-0,3050 mm/tahun termasuk ke dalam kategori good berdasarkan tabel ketahanan korosi relatif baja,.dengan demikian terdapat 44% atau 11 test point yang diprediksi tidak mencapai umur desain yaitu 15 tahun.